In-situ Fe isotope ratio determination in Fe-Ti oxides and sulfides from drilled gabbros and basalt from the IODP Hole 1256D in the eastern equatorial Pacific - Dziony, Wanja; Horn, Ingo; Lattard, Dominique; Koepke, Jürgen; Steinhoefel, Grit; Schuessler, Jan A.; Holtz, François (Chemical geology, 2014)
In-situ Fe isotope measurements have been carried out to estimate the impact of the hydrothermal metamorphic overprint on the Fe isotopic composition of Fe-Ti-oxides and Fe-sulfides of the different lithologies of the drilled rocks from IODP Hole 1256D (eastern equatorial Pacific; 15Ma crust formed at the East Pacific Rise). Most igneous rocks normally have a very restricted range in their 56Fe/54Fe ratio. In contrast, Fe isotope compositions of hot fluids (>300°C) from mid-ocean-ridge spreading centers define a narrow range that is shifted to lower δ56Fe values by 0.2‰-0.5‰ as compared to igneous rocks. Therefore, it is expected that mineral phases that contain large amounts of Fe are especially affected by the interaction with a fluid that fractionates Fe isotopes during exsolution/precipitation of those minerals. We have used a femtosecond UV-Laser ablation system to determine mineral 56Fe/54Fe ratios of selected samples with a precision of <0.1‰ (2σ level) at micrometer-scale. We have found significant variations of the δ56FeIRMM-014 values in the minerals between different samples as well as within samples and mineral grains. The overall observed scale of δ56Femagnetite in 1256D rocks ranges from −0.12 to +0.64‰, and of δ56Feilmenite from −0.77 to +0.01‰. Pyrite in the lowermost sheeted dike section is clearly distinguishable from the other investigated lithological units, having positive δ56Fe values between +0.29 and +0.56‰, whereas pyrite in the other samples has generally negative δ56Fe values from −1.10 to −0.59‰. One key observation is that the temperature dependent inter-mineral fractionations of Fe isotopes between magnetite and ilmenite are systematically shifted towards higher values when compared to theoretically expected values, while synthesized, well equilibrated magnetite-ilmenite pairs are compatible with the theoretical predictions. Theoretical considerations including β-factors of different aqueous Fe-chlorides and Rayleigh-type fractionations in the presence of a hydrous, chlorine-bearing fluid can explain this observation. The disagreement between observed and theoretical equilibrium fractionation, the fact that magnetite, in contrast to ilmenite shows a slight downhole trend in the δ56Fe values, and the observation of small scale heterogeneities within single mineral grains imply that a general re-equilibration of the magnetite-ilmenite pairs is overprinted by kinetic fractionation effects, caused by the interaction of magnetite/ilmenite with hydrothermal fluids penetrating the upper oceanic crust during cooling, or incomplete re-equilibration at low temperatures. Furthermore, the observation of significant small-scale variations in the 56Fe/54Fe ratios of single minerals in this study highlights the importance of high spatial-resolution-analyses of stable isotope ratios for further investigations.